Synthesis of polysulfone-b-polystyrene block copolymers by mechanistic transformation from condensation polymerization to free radical polymerization - Dizman, Cemil; Kahveci, Muhammet U.; Yagci, Yusuf (SPRINGER, 2013)
Synthesis of polysulfone-b-polystyrene (PSU-b-PS) block copolymers by a combination of condensation polymerization and free radical polymerization processes are described. First, a new macroazoinitiator (MAI) containing polysulfone (PSU) units was prepared by direct esterification of 4,4-azobis(4-cyanopentanoic acid) with alpha,omega-hydroxyl PSU telechelics at ambient conditions. The macroinitiator was then used in conventional free radical polymerization of styrene leading to the formation of desired block copolymers. In this process, initiating macroradicals were generated by thermal cleavage of the azo group present in the macroazoinitiator structure. The precursor polysulfone macroazoinitiator (PSU-MAI) and resulting block copolymers were characterized by spectral analysis using FT-IR, H-1-NMR, GPC, TGA, and DSC.
Keywords: Block copolymer; Condensation polymerization; Free radical polymerization; Macroazoinitiator; Polysulfone; Polystyrene; POLY(ARYLENE ETHER SULFONE); PROTON-EXCHANGE MEMBRANES; AMPHIPHILIC GRAFT-COPOLYMERS; AZO-OXOCARBENIUM INITIATOR; MIKTOARM STAR COPOLYMERS; CATIONIC-POLYMERIZATION; PROTEIN ADSORPTION; CLICK CHEMISTRY; TERMINATED POLYTETRAHYDROFURAN; THERMAL-PROPERTIES; Polymer Science